Martin Luther: the life and lessons - Mansch, Larry D. (McFarland & Company, Inc., Publishers, 2016)
"Combining biographical narrative and analytical essays, this book provides a view of Martin Luther's life and times, along with an examination of the radical theology that sparked the Reformation and changed the Christian world forever. Drawing on sources new and old, the authors retell the fascinating, turbulent story of the Great Reformer from a historical point of view"--